Коррозионно-электрохимическое поведение износостойких нанокристаллических покрытий в растворе NaCl - Севидова, Елена Константиновна; Степанова, Ирина Игоревна; Рязанова-Хитровская, Наталия Владимировна (Национальный технический университет "Харьковский политехнический институт", 2015)
Проведены исследования коррозионно-электрохимической активности нанокристаллических (d ~ 15-25 нм) покрытий TiN на подложке из стали 12Х18Н10Т в 3%-ом растворе NaCl. Установлено, что в диапазоне толщин 1…8 мкм покрытия, сформированные вакуумным методом, имеют сквозные дефекты. Анодная активность системы подложка-покрытие зависит от толщины TiN и давления азота, влияющего на уровень остаточных напряжений в них.

The corrosion-protective properties of noncrystalline coatings of TiN (a - 15...25 nanomеters) concerning to the substrate of stainless steel 12Х18Н10Т was studied in a 3% solution of NaCl using electro-chemical method. It is shown that in the range of the thickness - 1-8 micron coatings formed by vacuum-arc method are porous, and their protective properties mainly depend on the thickness and the factors which affect the level of residual stresses in them - the deposition rate and the reaction gas pressure.
Corrosion-electrochemical behaviour of wearproof nanokristallichesky coverings in the solution NaCl
Keywords: нитрид титана; защитные свойства; titanium nitride; protective properties